Projeto, construção e teste de instrumentação eletrônica para avaliação do desempenho de tratores agrícolas - Russini, Alexandre (2009)
The objective of this work was to design, construct and test an electronic instrumentation acquisition and storage of data, regarding the performance of the agricultural tractors during operations to field. Was realized the design informational, conceptual, preliminary and detailed of the instrumentation to be built, looking to the installation of sensor for measure of the speed of the drive wheels and speed of the tractor, flow meter for determination of the consumption of fuel and a load cell for measure of the traction force. All the instrumentation was installed was set up in a tractor Massey Ferguson model Advanced 290 Shuttle with front wheel drive, and the values obtained by the electronic equipments that constitute the system of sensor are driven a system of storage of data based on a datalogger. Later those data were collected through the software PC200W®, who it s characterized by being base software that there is a programming developed exclusively for this work. This tractor was submitted to field tests, where it was possible to verify the operation and the quality of the obtained data. The data considered rude, because they are present in the text, we need to transfer they to an electronic spreadsheet of Microsoft Excel® for us to be later organized, interpreted in a clear and objective way. At the end of this work, it is ended that is possible to determine the performance of the agricultural tractors through an electronic instrumentation, obtaining data that represent the conditions of the test in that the tractor was submitted.